An Investigation of Bottled Water Use and Caries in the Mixed Dentition - Barbara Broffitt, MS; Steven M. Levy, DDS, MPH; John J. Warren, DDS, MS; (Blackwell Synergy, 2007)
Bottled water consumption in the United States has greatly increased in the past decade.